KEPEMIMPINAN TRANSFORMASIONAL KYAI PADA LEMBAGA PENDIDIKAN ISLAM - Bashori, Bashori (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
This research presents about Kyai's transformational leadership in managing Islamic educational institutions in order to have strong excellence and competitiveness, in the midst of competition between educational institutions. The study of Kyai's leadership has its own uniqueness, considering that Kyai is a charismatic figure and has a high spirituality value for a community of people, who must play a dual role as a leader and also a manager in the educational institution he leads, namely pesantren. This research uses a qualitative approach to with library research. The data analysis technique uses content analysis. The results showed that; Kyai as a transformative leader in managing his educational institutions, especially pesantren has four dimensions; First, charismatic leadership, where Kyai's position is used as a role model by his followers, secondly inspirational motivation, where a Kyai is able to inspire and motivate followers to achieve the goals of pesantren, third, intellectual stimulation which is able to foster ideas and ideas from others to advance pesantren educational institutions, fourth, individualized consideration, in which a Kyai wants to listen to the aspirations and input of others for the development of the educational organization he leads.